Analysis of Surface Wind Speed at Sultan Thaha Jambi Airport for The Period 2019-2023 using The Windrose Method - Febryani Putry (Journal of Experimental and Applied Physics, 2026)
This study aims to analyze the direction and speed of surface winds at Sultan Thaha Airport in Jambi at an altitude of 10 meters during the period 2019–2023 using the wind rose analysis using WRPLOT View software. Wind direction and speed are meteorological parameters that significantly impact flight safety and operational efficiency, particularly during takeoff and landing phases. This study is motivated by the importance of understanding wind patterns in supporting technical decision-making by airport authorities, such as determining runway direction and issuing early warnings about hazardous crosswinds. The data used in this study are secondary data sourced from the Jambi BMKG Climatology Station, which include daily wind direction and speed parameters and were processed using WRPLOT View software. The results show that the dominant wind direction changes seasonally, from northwest in January–March to southeast in May–September, influenced by monsoon winds. The average wind speed ranges from 8.6 to 9.3 knots, with a maximum speed of 29.16 knots recorded on September 6, 2019. Therefore, the research results can support the improvement of aviation operational safety, particularly in decision-making regarding runway direction and aircraft maneuvering strategies.